Magnetic Field Distribution and Energy Losses in a Permanent Magnet Linear Synchronous Motor Under Stick-Slip Friction - Paweł Olejnik; Yared D. Desta; Marcin Mydłowski (Energies)
This study investigates the modeling and dynamic analysis of three coupled electromechanical systems, emphasizing interactions between a magnetic linear drive and frictional contact with flat springs. The experimental setup includes a table driven by a three-phase permanent magnet linear synchronous motor (PMLSM) using an LMCA4 inductor, LMCAS3 magnetic track, and Xenus XTL controller. Mechanical phenomena such as stick-slip friction and impulsive loads are observed, particularly due to the rapid buckling of flat springs. These springs transition between sliding friction and fixation, impacting the motor’s operation during reciprocating velocity trajectories and generating acoustic emissions. Numerical simulations using COMSOL Multiphysics evaluate the magnetic field and system geometry in two- and three-dimensional spaces. Key findings include mechanical stick-slip vibrations, numerical modeling of the linear drive, and comparative analysis of experimental and simulated inductor current variations. Additionally, energy loss mechanisms under irregular loading conditions are assessed. The results highlight the coupling between friction-induced current changes and magnetic field variations, elucidating their impact on motor efficiency, vibration propagation, and acoustic emissions. The study provides insights into optimizing the design and reliability of coreless linear motors for precision applications under discontinuous loading.